National Institutes of Health Advancing Multimorbidity Research. Issue 7 (July 2021) - Salive, Marcel E.; Suls, Jerry; Farhat, Tilda; Klabunde, Carrie N.
Abstract : Background: Multimorbidity, the co-occurrence of 2 or more chronic diseases, is more common than having a single chronic disease, especially among persons age 65 years and older. The routine measurement of multimorbidity can facilitate a better understanding of potential causes and interactions and promote more effective treatment and improved outcomes. Objectives: To present a multimorbidity research framework and identify gaps in the research literature related to multimorbidity. Design: In preparation for an expert panel workshop convened in September 2018, planning committee members reviewed the literature and developed a guiding framework that informed the selection of topics and speakers. Results: The framework, grounded in a patient-centered approach, incorporates the concept of concordant and discordant comorbidity, and includes potential causes, interactions, and outcomes. This work informed workshop presentations and discussion related to identifying and selecting the best available multimorbidity instruments and determining future research needs. Conclusions: Multimorbidity research can be advanced by addressing gaps in study design and target populations, and by increasing attention to universal outcome measurement.